Transnational Networks & Aid Accountability: Post-Disaster Aid and Relief-Reconstruction Complex in Daanbantayan, Cebu - Chan, Angel (Archīum Ateneo, 2021)
Within complex governance, Typhoon Haiyan (Yolanda) has influenced the burgeoning landscape of partnerships between the local government, private corporations, and humanitarian agencies in post-disaster relief and reconstruction, wherein transnational donors and multiple non-governmental organizations have stayed beyond the relief phase and exceeded their traditional role as private actors. The aim of this case study was to describe the networks of Habitat French Village and Red Cross Village, post-Haiyan housing projects in Daanbantayan, Cebu, and to analyze the governance and practices of aid flows and aid accountability. Aside from the beneficiary communities and Municipality, the case areas also involve overlapping networks of transnational donors such as France-Philippines United Action (FPUA) and French Red Cross (CRF), implementers Habitat for Humanity Philippines (HFHP) and Philippine Red Cross (PRC), and contractors under HFHP. A documentary and thematic analysis based on indicators for strength of ties and participation is utilized to illustrate the multi-directional accountability of the networks. The study has demonstrated that partnerships in networks have become a cornerstone in post-disaster relief and reconstruction. Even with complexities, a strong strength of ties and active beneficiary participation, aid governance can be shaped for the better. Distances in accountability can still be addressed with efficient communication and good governance. Choosing the right partners, close coordination, following through a contract, and community organization are vital to address any needs and services for affected communities.